UNVEILING GENDER IDEOLOGY IN ENGLISH TEXTBOOKS PUBLISHED BY THE INDONESIAN MINISTRY OF EDUCATION AND CULTURE - Yeli Zastika; Syahrul Ramadhan; Yuli Tiarina (Universitas PGRI Sumatera Barat, 2025)
This study examines the construction of gender ideology in English textbooks published by the Indonesian Ministry of Education and Culture in 2022. As official pedagogical documents, the textbooks play a strategic role in shaping students' gender understanding. This study aimed to identify and analyze gender representations in text and images to uncover the gender ideologies underlying the materials' construction. To answer the research questions, high school textbooks for grades X, XI, and XII served as data sources. Using a qualitative design with documentation and discourse analysis techniques, this study classified verbal and visual excerpts into ideological frameworks through a multimodal discourse analysis approach. The findings revealed three main ideologies: egalitarian, intensive parenting, and moderate traditional. Egalitarian ideology is reflected in the representation of women and men as professional, high-achieving, resilient, and creative subjects; intensive parenting is evident through the collaborative division of caregiving roles, while moderate traditional ideology is evident in the continued dominance of women in certain domestic tasks. These three ideologies indicate a hybrid gender discourse that reflects the negotiation between progressive and traditional values in government-published textbooks. Practically, these findings encourage the need for gender sensitivity audits in textbook development and critical pedagogy in the classroom. Theoretically, this research contributes to strengthening the understanding that gender representation in educational media is dynamic, layered, and reflects broader social changes in the context of national education.